2018
DOI: 10.1007/s12011-018-1423-x
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Trace Metals in Electronic Cigarette Aerosols—a Systematic Review

Abstract: Electronic cigarettes (ECs) are essentially nicotine delivery devices that mimic the appearance of a conventional cigarette (CC). Lately, they have been marketed as tools for quitting smoking. Even though they are promoted as safe alternatives to CC, they are not devoid of hazardous components. Literature reveals that the EC aerosols and e-liquids are a potential source of elements that induce and promote development of chronic conditions. These include trace metals which are leached from their core assembly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 84 publications
0
100
0
1
Order By: Relevance
“…Youth describe the contents of vaping oils as harmless "water vapor, " which may be "good" for them [21]. e vapor from these vaping devices may contain particulate matter, as well as chemicals such as carbonyls, volatile organic compounds, and toxic metals, which have been linked to dyspnea, cough, upper airways irritation, asthma, pneumonia and lung cancer [22,23]. Inhaling aerosols has been shown to increase airway resistance and decrease FEV1 in healthy nonsmokers [24].…”
Section: Discussionmentioning
confidence: 99%
“…Youth describe the contents of vaping oils as harmless "water vapor, " which may be "good" for them [21]. e vapor from these vaping devices may contain particulate matter, as well as chemicals such as carbonyls, volatile organic compounds, and toxic metals, which have been linked to dyspnea, cough, upper airways irritation, asthma, pneumonia and lung cancer [22,23]. Inhaling aerosols has been shown to increase airway resistance and decrease FEV1 in healthy nonsmokers [24].…”
Section: Discussionmentioning
confidence: 99%
“…Reviews on e-cigarettes have summarized e-cigarette development (Cooke et al 2015;Glasser et al 2017), their impact on decreasing smoking use (Kalkhoran and Glantz 2016;Rahman et al 2015), health and physiological effects Pisinger and Døssing 2014;Zucchet et al 2017), and effects of vaping on indoor air quality (Fernández et al 2015;Zainol Abidin et al 2017). Some of these reviews reported on metal levels; in addition, two systematic reviews have specifically evaluated metals/metalloids in cig-a-like cartomizers (Mishra et al 2017) and in e-cigarette aerosols (Gaur and Agnihotri 2019). Overall, previous reviews reporting on e-cigarette-related metal/metalloid levels focused on aerosols, e-liquids, or human biosamples, separately.…”
Section: Introductionmentioning
confidence: 99%
“…Vaporized e-liquid solution is contaminated with various metals, such as aluminum, arsenic, cadmium, chromium, copper, iron, manganese, nickel, lead and zinc, which pose a threat to human health [44]. In addition, trace metals can also be delivered to the aerosol through components of the electronic nicotine delivery system, such as the atomizer and batteries; this contamination may be exacerbated by the high temperatures involved in the production of the aerosol [45]. Part of the heavy metals present in vapor, such as lead, are derived from Nicotiana tabacum, the source of nicotine in tobacco, which absorbs pollutants from the environment during its growth [46].…”
Section: The Mechanisms Of E-cigarette Actionmentioning
confidence: 99%